LEARNING ARABIC LANGUANGE BY USING LAQU (Pembelajaran Bahasa Arab dengan LAQU) - Wilda Rihlasyita (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2020)
Nowadays, the learning of foreign languages, especially Arabic, continues to experience rapid progress in the field of technology. The use of technology-based media must be further developed, in order to foster students’ enthusiasm in learning Arabic. One method that is being developed at this time is LAQU (Learning Arabic For Qur'an Understanding). LAQU is the first product of Arabic learning that is devoted to the understanding of the Al-Qur'an with the AMALI method. It consist of: Amalkan (Natural), Mainkan (Play), Aplikasikan (Apply), Lagukan (Sing), and Imajinasikan (Imaginative). Language learning is analogous to the use of train parts, such as cars and locomotives, making learning Arabic very easy and fun. Because this media is packed with visual, kinesthetic and auditory approaches, not only with memorizing method like the existing methods. With illustrations, games and songs at LAQU, it is expected that learning Arabic will be easier and more enjoyable. This method is suitable to be used by all people, ranging from children, parents, teachers, and anyone who wants to learn Arabic easily, with examples of sentences taken directly from the Qur'an. This paper will be focus on the discussion of “Changes in verbs with LAQU”. The use of LAQU in Arabic learning is proven to be able to help students to understand complex concepts in Arabic, especially in understanding grammar which includes nahwu, sharf, iʻrab, and others. It is expected that this method can be used as a reference for instructors of Arabic to make Arabic language learning easier and more enjoyable. Keywords: Arabic Language, LAQU